Antibacterial Activity of Phytochemicals in Ficus thonningii Leaves Extracts Against Some Selected Pathogenic Bacterial Prevalent in Sickle Cell Anemia - Ijoma, Ikechukwu; Egbulefu Ajiwe, Vincent Ishmael (Jordan Journal of Pharmaceutical Sciences, 2023)
Sickle cell anemia (SCA) is caused by point mutation involving substitution of valine by glutamic acid, clinical cause of this is that SCA patients are immunocompromised hence, prone to bacterial infections. Escherichia coli, Klebsiella. pneumoniae, Salmonella typhi, Streptococcus pneumoniae and Staphylococcus aureus are some of the bacterial associated with SCA. Here we investigated the antibacterial activity of extracts of Ficus thonningii leaves used by ethnomedicinal practitioners in the management of infections in SCA patients. The antimicrobial activity was determined based on average diameter of zone of inhibition (AVDZI), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) while, structure of compounds FTH1 (Bergapten), FTH2 (Protocatechuic acid) and FTH3 (Methyl ferulate) were identified based on Nuclear Magnetic Resonance (NMR) analysis. The results indicated that the crude extracts of methanol (MCE), hexane (HCE), chloroform (CCE) and methanol-water (MWCE) had AVDZI of ≥ 12.1 ± 0.12 mm, ≥ 11.0 ± 0.00 mm, ≥ 10.2 ± 0.25 mm and ≥ 12.1 ± 0.21 mm respectively while the isolated compounds FTH1, FTH2 and FTH3 had AVDZI of ≥ 10.1 ± 0.10 mm, ≥ 9.1 ± 0.12 mm, ≥ 7.1 ± 0.24 mm respectively. The AVDZI results was tested for statistical significance using one way ANOVA and Tukey Posthoc test, and was considered significant at p < 0.05. Our findings suggested that F. thonningii leaves extracts including compounds isolated from them are potential antibacterial agent and justify their use as antibacterial prophylactics in the management of infections in SCA patients by ethnic people in Nigeria